2003
DOI: 10.1111/1467-9280.01420
|View full text |Cite
|
Sign up to set email alerts
|

Serial Expertise of Rhesus Macaques

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 32 publications
10
141
0
Order By: Relevance
“…Recently, researchers have shown that rhesus monkeys can learn a sequence of arbitrary images and subsequently apply that knowledge to answer new questions about that sequence (40). The experiments of series III demonstrate that honey bees possess a similar capability but in a simpler form.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, researchers have shown that rhesus monkeys can learn a sequence of arbitrary images and subsequently apply that knowledge to answer new questions about that sequence (40). The experiments of series III demonstrate that honey bees possess a similar capability but in a simpler form.…”
Section: Discussionmentioning
confidence: 97%
“…of human cognitive phenomena that are beyond the scope of traditional chaining theory. These include serial expertise [15], knowledge of the ordinal position of list items [15][16][17], numerical sequences [18][19][20] and distance and magnitude effects [21][22][23]. This article will summarize some recent research on those topics and indicate how it has led to animal models of cognitive phenomena that, until recently, have been regarded as exclusively human.…”
Section: Simultaneous Chaining Paradigm (Scp)mentioning
confidence: 99%
“…Details of this training can be found in Terrace, Son, and Brannon (2003). Prospero was also trained on a sequential match-to-sample task in which the stimuli were photographs.…”
Section: Previous Trainingmentioning
confidence: 99%